3D‐Epigenomic Regulation of Gene Transcription in Hepatocellular Carcinoma. Issue 4 (29th June 2022) - Feng, Yuliang; Wang, Ping; Cai, Liuyang; Zhan, Meixiao; He, Fan; Wang, Jiahui; Li, Yong; Gega, Eva; Zhang, Wei; Zhao, Wei; Xin, Yongjie; Chen, Xudong; et al.
Abstract: The fundamental cause of transcription dysregulation in hepatocellular carcinoma (HCC) remains elusive. To investigate the underlying mechanisms, comprehensive 3D‐epigenomic analyses are performed in cellular models of THLE2 (a normal hepatocytes cell line) and HepG2 (a hepatocellular carcinoma cell line) using integrative approaches for chromatin topology, genomic and epigenomic variation, and transcriptional output. Comparing the 3D‐epigenomes in THLE2 and HepG2 reveal that most HCC‐associated genes are organized in complex chromatin interactions mediated by RNA polymerase II (RNAPII). Incorporation of genome‐wide association studies (GWAS) data enables the identification of non‐coding genetic variants that are enriched in distal enhancers connecting to the promoters of HCC‐associated genes via long‐range chromatin interactions, highlighting their functional roles. Interestingly, CTCF binding and looping proximal to HCC‐associated genes appear to form chromatin architectures that overarch RNAPII‐mediated chromatin interactions. It is further demonstrated that epigenetic variants by DNA hypomethylation at a subset of CTCF motifs proximal to HCC‐associated genes can modify chromatin topological configuration, which in turn alter RNAPII‐mediated chromatin interactions and lead to dysregulation of transcription. Together, the 3D‐epigenomic analyses provide novel insights of multifaceted interplays involving genetics, epigenetics, and chromatin topology in HCC cells. Abstract : THLE2 cells of normal liver hepatocytes and HepG2 cells of hepatocellular carcinoma (HCC) are comprehensively analyzed via integrated approaches including ChIA‐PET for 3D‐genome mapping and RNA‐seq, ChIP‐seq, and whole genome bisulfite sequencing for epigenome mapping, thus the 3D‐epigenome. The comparative analyses of the 3D‐epigenomes for normal hepatocytes and HCC cells reveal HCC‐associated genes for suppressing normal functions (HCC‐suppressed genes) in hepatocytes and activating new properties (HCC‐specific genes) in HCC.